Peran Mediasi Penerapan Sistem E-Filing terhadap Keterkaitan Sikap terhadap E-Filing dan Kepatuhan Wajib Pajak - Siti Nuryanah; Nurhapsari, Risma (Universitas Sains dan Teknologi Komputer, 2026)
This study aims to examine the extent to which taxpayers’ attitudes toward e-filing influence tax compliance, with the implementation of e-filing positioned as a mediating variable among employees of PT Selalu Cinta Indonesia (SCI) registered at the Primary Tax Office (KPP Pratama) of Salatiga City. The population comprised 18,244 employees, from which a sample of 100 respondents was selected using purposive sampling. Data were processed and analyzed using simple linear regression and path analysis. The results indicate that attitudes toward e-filing have a significant effect on taxpayer compliance (t = 7.708; sig. < 0.001) and also significantly influence the level of e-filing implementation (t = 7.644; sig. < 0.001). Furthermore, the implementation of e-filing has a significant impact on taxpayer compliance (t = 150.765; sig. < 0.001). Additional findings reveal that e-filing implementation acts as a partial mediator in the relationship between attitudes toward e-filing and taxpayer compliance, with a total effect value of 1.225. Overall, these findings reinforce the Theory of Planned Behavior framework, which posits that positive attitudes toward a system can foster the formation of specific behaviors, particularly in the context of tax compliance.